The Influence of Accounting Information Systems and Understanding of Accounting Standards on the Quality of Financial Reports Moderated by Locus of Control for Small and Medium Enterprises Kabupaten Batubara - Lufriansyah, Lufriansyah; Alis, Alis (AIBPM Publisher, 2023)
The purpose of this study was to determine and analyze the influence of accounting information systems and understanding of accounting standards on the quality of financial reports, moderated by locus of control, directly or indirectly. The approach used in this research is a causal approach. The population in this study were all SMEs in Batu Bara district. The sample in this study used the slovin formula of 86 UMKM actors in the Batu Bara district. Data collection techniques in this study using a questionnaire technique. Data analysis techniques in this study used a quantitative approach using statistical analysis using the Auter Model Analysis test, Inner Model Analysis, and Hypothesis Testing. Data processing in this study uses the PLS (Partial Least Square) software program. The results of this study prove that directly accounting information systems and understanding of accounting standards have a significant effect on the quality of financial reports, and indirectly locus of control is not able to moderate the effect of accounting information systems and understanding of accounting standards on the quality of reports of small and medium business actors in Batu Bara district